2014
DOI: 10.1111/exd.12456
|View full text |Cite
|
Sign up to set email alerts
|

Merkel cells and touch domes: more than mechanosensory functions?

Abstract: The touch dome is an innervated structure in the epidermis of mammalian skin. Composed of specialized keratinocytes and neuroendocrine Merkel cells, the touch dome has distinct molecular characteristics compared to the surrounding epidermal keratinocytes. Much of the research on Merkel cell function has focused on their role in mechanosensation, specifically light-touch. Recently, more has been discovered about Merkel cell molecular characteristics and their cells of origin. Here we review Merkel cell and touc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 62 publications
(64 reference statements)
3
30
0
Order By: Relevance
“…Merkel cells of different shapes, including round or oval cells as well as dendritic cells, were noted in ESS in vivo (Fig 1). This is consistent with previous observations of Merkel cells in humans [26] and rodents [4345]. KRT20 and KRT18 exhibited a perinuclear localization pattern in Merkel cells, although they were also localized to cellular projections in dendritic Merkel cells.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Merkel cells of different shapes, including round or oval cells as well as dendritic cells, were noted in ESS in vivo (Fig 1). This is consistent with previous observations of Merkel cells in humans [26] and rodents [4345]. KRT20 and KRT18 exhibited a perinuclear localization pattern in Merkel cells, although they were also localized to cellular projections in dendritic Merkel cells.…”
Section: Resultssupporting
confidence: 93%
“…Afferents expressing NF-H, which is reportedly found in more mature, myelinated neurons, were observed in the dermis of ESS at 4 weeks after grafting, but were not found in association with Merkel cells until 8 weeks after grafting. As previously observed in rodent and human skin [26, 43, 45], Merkel cells in ESS were heterogeneous in shape, displaying either a dendritic phenotype or more oval shape. It has been reported that in rodents, oval shaped Merkel cells tend to be innervated whereas dendritic cells may not be associated with nerves [43].…”
Section: Discussionsupporting
confidence: 67%
“…This is a novel response that we hypothesize is secondary to mild superficial wound healing. We confirmed that these new Merkel cells arise from touch dome keratinocytes, as has been previously reported (Doucet et al, 2013; Xiao et al, 2014). …”
Section: Discussionsupporting
confidence: 92%
“…Quantitative increase of MCs in psoriatic lesional skin signifies its role in cutaneous immunology. [ 53 ]…”
Section: Functionsmentioning
confidence: 99%